2019
DOI: 10.18632/aging.102326
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and transcriptomic profile in hippocampus of young mice after multiple neonatal exposures to sevoflurane

Abstract: Children with repeated inhalational anesthesia may develop cognitive disorders. This study aimed to investigate the transcriptome-wide response of hippocampus in young mice that had been exposed to multiple sevoflurane in the neonatal period. Mice received 3% sevoflurane for 2 h on postnatal day (PND) 6, 8, and 10, followed by arterial blood gas test on PND 10, behavioral experiments on PND 31–36, and RNA sequencing (RNA-seq) of hippocampus on PND 37. Functional annotation and protein-protein interaction analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 77 publications
(70 reference statements)
3
28
0
Order By: Relevance
“…Inactivating the function may affect presynaptic action potential, increase calcium influx and neurotransmitter release, impair neuron firing, and influence synaptic transmission (reviewed in [ 46 ]). It is congruent with the data from the animal model induced-sevoflurane to impair cognition, which reported downregulation of KCNA3 at the brain hippocampus, suggesting the essential role of this gene in learning and memory [ 47 ]. Moreover, in diabetic rats with reduced insulin receptor kinase activity, the downregulated KCNA3 expression was reported associated with memory loss [ 48 ].…”
Section: Discussionsupporting
confidence: 88%
“…Inactivating the function may affect presynaptic action potential, increase calcium influx and neurotransmitter release, impair neuron firing, and influence synaptic transmission (reviewed in [ 46 ]). It is congruent with the data from the animal model induced-sevoflurane to impair cognition, which reported downregulation of KCNA3 at the brain hippocampus, suggesting the essential role of this gene in learning and memory [ 47 ]. Moreover, in diabetic rats with reduced insulin receptor kinase activity, the downregulated KCNA3 expression was reported associated with memory loss [ 48 ].…”
Section: Discussionsupporting
confidence: 88%
“…Even though the effect of sevoflurane on cognition were controversial, such as the deleterious impact of sevoflurane exposure in the neonatal period [ 47 ], numbers of studies reported the protective effect of SP in varied IRI models. In myocardial IRI, SP reduces the production of mitochondrial ROS, increases the content of mitochondrial ATP, and thus reduces apoptosis through activating the JAK2-STAT3 pathway [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has elicited the functionality of RASD1 as a pivotal regulator in cognitive deficits [ 27 ]. Moreover, Sevoflurane has been elicited to be potential in attenuating cognitive deficits [ 28 ]. Essentially, Fleming et al .…”
Section: Discussionmentioning
confidence: 99%